2014
DOI: 10.1021/am503045b
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Imprinted Substrates Act as an Artificial Niche for Skin Regeneration

Abstract: Bioinspired materials can mimic the stem cell environment and modulate stem cell differentiation and proliferation. In this study, biomimetic micro/nanoenvironments were fabricated by cell-imprinted substrates based on mature human keratinocyte morphological templates. The data obtained from atomic force microscopy and field emission scanning electron microscopy revealed that the keratinocyte-cell-imprinted poly(dimethylsiloxane) casting procedure could imitate the surface morphology of the plasma membrane, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 70 publications
5
71
0
Order By: Relevance
“…This nano-imprinted topography derived from natural chondrocyte shapes acts as a shape cue and physical confining driving force which stimulates differentiation of stem cells to chondrocytes. The same results 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 were obtained from cell-imprinted substrates as morphological templates based on mature human keratinocyte 20 . The data acquired from atomic force microscopy and field emission scanning electron microscopy revealed that the chondrocyte (or keratinocyte)-cell-imprinted PDMS casting procedure could imitate the surface morphology of the plasma membrane, at typical dimensions ranging from the nanoscale to the macroscale, which may provide the required topographical cell fingerprints to induce differentiation.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This nano-imprinted topography derived from natural chondrocyte shapes acts as a shape cue and physical confining driving force which stimulates differentiation of stem cells to chondrocytes. The same results 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 were obtained from cell-imprinted substrates as morphological templates based on mature human keratinocyte 20 . The data acquired from atomic force microscopy and field emission scanning electron microscopy revealed that the chondrocyte (or keratinocyte)-cell-imprinted PDMS casting procedure could imitate the surface morphology of the plasma membrane, at typical dimensions ranging from the nanoscale to the macroscale, which may provide the required topographical cell fingerprints to induce differentiation.…”
Section: Introductionsupporting
confidence: 59%
“…After 3 h, 1 ml culture medium was added to cover the cells and incubation maintained for 2 weeks with medium exchange every 4 days. Gene expression analysis and immuno-staining were conducted in the same way as previously published 20 . Tables 1 and 2 show the list of primer sequences and antibodies, respectively.…”
Section: Cell Seeding On Imprinted Substrates and Characterizationsmentioning
confidence: 99%
“…The chain is in its native state and fully folded when all native contacts are formed. The permutation in the connectivity is done using the Heap algorithm 17 to ensure all conformations are surveyed and this is done for all 5 Â 10 6 conformations with different topological arrangements. This is verified through obtaining equal values in each topological state.…”
Section: Kinetic Monte Carlomentioning
confidence: 99%
“…We use a coarse-grained model of a linear self-avoiding polymer chain 17,18 to investigate how the topological states of the intrachain contacts are affected as the external molecule (chaperone) changes the chain's global topology. This is carried out by simulation setups in which the chaperone keeps the chain termini at a certain distance.…”
Section: Molecular Dynamics (Md)mentioning
confidence: 99%
“…Recently biomimetic materials for skin regeneration were fabricated through cell-imprinting during which mature human keratinocyte morphological templates 12.1 Biomaterials for Scaffolds and Skin Tissue were used [ 14 ]. The keratinocyte-imprinted polymeric nanostructure, prepared by casting, imitated very well the surface morphology of the plasma membrane.…”
Section: Biomaterials For Scaffolds and Skin Tissuementioning
confidence: 99%